Pesta Dusun Di Kecamatan Rambang Kapak Tengah - Putrisyah, Nadya; Agustina, Dhanty Rahmallah; Syarifuddin., Syarifuddin. (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2021)
This study aims to determine the purpose of implementing the Hamlet Party activities in Rambang Kapak Tengah District, Prabumulih City, and to understand how these activities are carried out and their current conditions. A unique aspect of this research is exploring the relationship between two traditions, namely the Sambai Begandai Tradition and the Nanggok Fish Tradition, in the context of the Hamlet Party activities. The study employs a qualitative method, where researchers collect, organize, and interpret the data obtained. Interviews and document studies supplement this approach. Essentially, the Hamlet Party is a form of gratitude the village community expresses for successfully completing a communal activity. It is a celebration filled with thankfulness and appreciation for the blessings of life that have been received.